Exogenous salicylic acid regulates organic acids metabolism in postharvest blueberry fruit - Jiang, Bo; Fang, Xiangjun; Fu, Daqi; Wu, Weijie; Han, Yanchao; Chen, Hangjun; Liu, Ruiling; Gao, Haiyan (Frontiers in Plant Science, 2022)
Fruit acidity is an essential factor affecting blueberry organoleptic quality. The organic acid content in blueberry fruit mainly contributes to fruit acidity. This study aims to evaluate the effect of exogenous salicylic acid (SA), the principal metabolite of aspirin, on the organoleptic quality and organic acid metabolism in rabbiteye blueberry (Vaccinium virgatum Ait, ‘Powderblue’) during cold storage (4 ℃). Results showed that SA-treated fruit reduced fruit decay and weight loss delayed fruit softening, and decline of total soluble solids (TSS). TA and total organic acid amounts stayed the same during the late storage period in SA-treated fruit. Four kinds of organic acid components, malic acid, quinic acid, citric acid, and succinic acid, were at higher levels in fruit treated by SA as compared to control. SA enhanced the activities of PEPC, NAD-MDH, and CS to promote the synthesis of malic acid and citric acid. Meanwhile, the activities of NADP-ME, ACL, and ACO, which participated in the degradation of malic acid and citric acid, were inhibited by SA. qPCR results also showed that the expression of VcPEPC, VcNAD-MDH, and VcCS genes were upregulated. In contrast, SA downregulated the expression of VcNADP-ME, VcACL, and VcACO genes. In conclusion, SA could regulate the key genes and enzymes that participated in organic acids metabolism to maintain the freshness of blueberry during cold storage, therefore minimizing the economic loss.